Plant parasitic nematodes and their management in the Maritime provinces of Canada - Kimpinski, J.; Thompson, L.S. (Phytoprotection, 1990)
This paper presents a review of the plant parasitic nematodes that are of concern in New Brunswick, Nova Scotia, and Prince-Edward-Island, and the approaches used to manage them. The root lesion nematode (Pratylenchus penetrans) is the only nematode species in the region that regularly reduces crop yields. The northern root-knot nematode (Meloidogyne hapla) occasionally causes damage to carrots (Daucus carota), but population levels of this nematode species usually are very low. The clover cyst nematode (Heterodera trifolii) is widespread, but has not caused any damage to crops in the region. Management procedures used to reduce the impact of plant parasitic nematodes in the Maritime provinces, e.g. crop rotations, nematicide treatments, enforcement of quarantine regulations, and tillage practices are discussed. A nematode advisory service is also considered.